Trinucleotide repeat length and clinical progression in Huntington's disease - (:unkn) unknown (My University, 2000)
Objective: Huntington's Disease is a progressive degenerative disorder having an expanded triplicate repeat in the gene IT-15 on chromosome 4. The interrelation between the trinucleotide repeat length and disease progression was studied. Methods: Five patients included in the study were evaluated by 'Quantified staging of functional capacity for Huntington's Disease patients' and age of disease onsets were determined. Progression rate was calculated and interrelationship between age of disease onset and repeat length; progression rate and repeat length were studied. Results: We found a statistically significant negative correlation between age of disease onset and trinucleotide repeat length (pearson r = -0.9514 p < 0.05). There was a statistically significant positive correlation between CAG repeat length and progression rate (pearson r = 0.8809, p < 0.05). Conclusion: Our study, conducted with a very limited number of patients, revealed the correlation between trinucleotide repeat length and disease progression. It like few similar studies in the literature, gave an impression of the important pathophysiological role of expanded CAG repeat during the entire course of the disease.
Keywords: Huntington's Disease; Prognosis; Progression rate; Trinucleotide repeat